Ablation-free agent for brake pad and brake pad

By coating the brake pad with an ablation-free agent containing zirconia, chromium oxide green and zinc powder on it, and curing it with plastic spraying treatment, the rust of metal brake pads in high temperature/high humidity/high salt environments is solved. Problem, the initial braking and rust resistance of the brake pads are improved.

CN119463620AActive Publication Date: 2025-02-18SHANDONG GOLD PHOENIX
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411715650.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-18
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

Metal brake pads are prone to rust in high temperature/high humidity/high salt environments, resulting in a degradation of brake performance, especially during sea transportation.

Method used

Ablation-free agent including ethanol, silicone modified phenolic resin, zirconium oxide, chromium oxide green, zinc powder, sodium bicarbonate, surfactant and thickener is applied to the friction block surface of the brake pad. And cured by plastic spraying to improve the rust and initial braking performance of the brake pads.

Benefits of technology

It effectively improves the initial braking performance and rust resistance of the brake pads, reduces rust problems, and reduces production costs. The ablation-free agent is environmentally friendly and non-toxic, simplifying the process flow.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463620A_ABST
    Figure CN119463620A_ABST
Patent Text Reader

Abstract

The invention provides an ablating-free agent for a brake pad and the brake pad, and relates to the technical field of automobile parts. The ablating-free agent is prepared from the following components in percentage by mass: 15.0 to 25.0 weight percent of ethanol, 4.0 to 8.0 weight percent of organic silicon modified phenolic resin, 45.0 to 60.0 weight percent of zirconium oxide, 5.0 to 8.0 weight percent of chromium oxide green, 6.0 to 10.0 weight percent of zinc powder, 3.0 to 6.0 weight percent of sodium bicarbonate, 1.0 to 2.0 weight percent of surfactant and 2.0 to 4.0 weight percent of thickening agent. The ablation-free agent for the brake pad not only can improve the initial brake performance of the brake pad, but also can improve the rust resistance of the brake pad, is environment-friendly and non-toxic, is simple to prepare, and can greatly reduce the cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of automobile parts, and in particular to an ablation-free agent for a brake pad and a brake pad. Background Art

[0002] Brake pads are the most critical safety parts in the braking system of a car and are also important components to ensure the safety of the driver. Commonly used automobile brake pads can be divided into metal type and non-asbestos organic (NAO) type according to the friction material. Compared with the NAO type, metal friction materials have good friction and wear characteristics and higher thermal conductivity, so they are widely used in the market. However, metal friction materials are exposed to high temperature / high humidity / high salt environment for a long time, and the iron components in the friction materials are prone to rust. Specifically, this is because the iron material components undergo chemical / electrochemical reactions in this environment and are oxidized to iron oxides. The above situation is particularly prominent during sea transportation. The high temperature / high humidity / high salt environment during long-term sea transportation makes brake pads prone to rust problems.

[0003] Normally, after replacing a new brake pad, a running-in period of about 200 kilometers is required. This is mainly because after replacing the new brake pad, the brake pad and the brake disc cannot achieve the best contact. Due to insufficient contact area, the braking performance is affected, resulting in the so-called "unable to stop". Therefore, it is also particularly important to improve the initial braking performance of the brake pad. Summary of the invention

[0004] In view of the above problems existing in the prior art, the present invention provides an ablation-free agent for a brake pad and a brake pad to improve the rust-proof ability of the brake pad.

[0005] To achieve the above-mentioned purpose and other related purposes, the first aspect of the present invention provides an ablation-free agent for brake pads. In terms of the mass percentage of the ablation-free agent, the ablation-free agent includes the following components: 15.0-25.0wt% of ethanol, 4.0-8.0wt% of silicone-modified phenolic resin, 45.0-60.0wt% of zirconium oxide, 5.0-8.0wt% of chromium oxide green, 6.0-10.0wt% of zinc powder, 3.0-6.0wt% of sodium bicarbonate, 1.0-2.0wt% of surfactant, and 2.0-4.0wt% of thickener.

[0006] In one embodiment of the present invention, the gel time of the organosilicon-modified phenolic resin at 165° C. is 30 to 51 seconds.

[0007] In one embodiment of the present invention, the D50 of the zirconium oxide is 1.5-6.0 μm.

[0008] In one embodiment of the present invention, the zinc powder is flake zinc powder, and the D50 of the zinc powder is 13-45 μm.

[0009] In one embodiment of the present invention, the surfactant includes any one of polyethylene glycol octylphenyl ether and fatty alcohol polyoxyethylene ether. The thickener includes any one of hydroxyethyl cellulose and polyvinyl alcohol.

[0010] A second aspect of the present invention provides a brake pad, comprising a friction block and a steel back, wherein the surface of the friction block is coated with a non-ablative coating made of the non-ablative agent for the brake pad.

[0011] In one embodiment of the present invention, the preparation of the ablation-free coating comprises the following steps:

[0012] Preparation of the ablation-free agent: placing ethanol, organosilicon-modified phenolic resin, zirconium oxide, chromium oxide green, zinc powder, sodium bicarbonate, a surfactant, and a thickener in a blender according to the raw material ratio and stirring evenly to obtain the ablation-free agent;

[0013] Ablation-free agent coating: the ablation-free agent is uniformly coated on the surface of the friction block, and dried naturally to form an ablation-free coating on the surface of the friction block.

[0014] In one embodiment of the present invention, the rotation speed of the stirrer is 200-240 r / min, and the stirring time is 5-7 min.

[0015] In one embodiment of the present invention, the coating thickness of the ablation-free agent is 0.1-0.2 mm.

[0016] In one embodiment of the present invention, a protective layer formed by spraying is provided on the surface of the steel back away from the ablation-free coating, the temperature of the spraying is 180-220° C., and the time of the spraying is 20-30 minutes.

[0017] The ablative-free agent for brake pads of the present invention is added with zirconium oxide, chromium oxide green, zinc flake powder, and sodium bicarbonate, which can improve the initial braking performance of the brake pads. The organosilicon-modified phenolic resin-zinc powder-sodium bicarbonate ternary composite can improve the hydrophobicity of the ablative-free agent matrix and the rust-proof performance of the brake pads through the synergistic effect of organosilicon-modified phenolic resin, zinc powder, and sodium bicarbonate. In addition, the ablative-free agent of the present invention does not contain toxic reagents, is environmentally friendly and non-toxic, and is easy to prepare; further, when the ablative-free agent is coated on the brake pad, it can be directly coated, and the curing of the ablative-free agent can be completed by plastic spraying, eliminating the additional high-temperature curing process, which can greatly reduce the cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only some embodiments of the present invention. For ordinary technicians in this field, other embodiments can be obtained based on these drawings without paying creative work.

[0019] Figure 1 FIG. 1 is a flow chart of preparing the ablation-free coating of the brake pad in one embodiment of the present invention. DETAILED DESCRIPTION

[0020] The following is an explanation of the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the features in the following embodiments and the embodiments can be combined with each other without conflict. It should also be understood that the terms used in the embodiments of the present invention are intended to describe specific embodiments, rather than to limit the scope of protection of the present invention. The test methods for which specific conditions are not specified in the following examples are usually carried out under conventional conditions or according to the conditions recommended by the manufacturers.

[0021] When numerical ranges are given in the embodiments, it should be understood that unless otherwise specified in the present invention, both endpoints of each numerical range and any value between the two endpoints can be selected. Unless otherwise defined, all technical and scientific terms used in the present invention are familiar to those skilled in the art and the description of the present invention, and any method, device and material of the prior art similar or equivalent to the method, device and material in the embodiments of the present invention can also be used to implement the present invention.

[0022] It should be noted that the terms such as "upper", "lower", "left", "right", "middle" and "one" etc. used in this specification are only for the convenience of description and are not intended to limit the scope of implementation of the present invention. Changes or adjustments to their relative relationships, without substantially changing the technical content, should also be regarded as the scope of implementation of the present invention.

[0023] The invention provides an ablation-free agent for a brake pad. The ablation-free agent comprises the following components, measured by mass percentage of the ablation-free agent: 15.0-25.0wt% of ethanol, 4.0-8.0wt% of organosilicon-modified phenolic resin, 45.0-60.0wt% of zirconium oxide, 5.0-8.0wt% of chromium oxide green, 6.0-10.0wt% of zinc powder, 3.0-6.0wt% of sodium bicarbonate, 1.0-2.0wt% of a surfactant and 2.0-4.0wt% of a thickener.

[0024] In one embodiment, the gel time of the organosilicon-modified phenolic resin at 165° C. is 30 to 51 seconds, such as any value within the range of 30 seconds, 40 seconds, 45 seconds, or 51 seconds.

[0025] In one embodiment, D50 of zirconium oxide is 1.5-6.0 μm, for example, any value within the range of 1.5-6.0 μm, such as 1.5 μm, 3.0 μm, 5.0 μm or 6.0 μm.

[0026] In one embodiment, the zinc powder is flake zinc powder, and D50 of the zinc powder is 13-45 μm, for example, any value within the range of 13-45 μm, such as 13 μm, 20 μm, 30 μm, 40 μm or 45 μm.

[0027] In one embodiment, the surfactant includes any one of polyethylene glycol octylphenyl ether and fatty alcohol polyoxyethylene ether. In other embodiments, the surfactant may also be other types of surfactants commonly used in the art.

[0028] In one embodiment, the thickener includes any one of hydroxyethyl cellulose and polyvinyl alcohol. In other embodiments, other commonly used thickeners in the art may also be selected.

[0029] The present invention also provides a brake pad, which includes a friction block and a steel back, the friction block and the steel back are fitted and fixed, and the friction block is coated with an ablation-free coating made of the above-mentioned ablation-free agent. Zirconium oxide, chromium oxide green, flake zinc powder, and sodium bicarbonate are added to the ablation-free agent to improve the initial braking performance of the brake pad. The organosilicon-modified phenolic resin-zinc powder-sodium bicarbonate ternary composite can improve the hydrophobicity of the ablation-free agent matrix and the rust-proof performance of the brake pad through the synergistic effect of organosilicon-modified phenolic resin, zinc powder, and sodium bicarbonate. Therefore, the brake pad of the present application has both good initial braking performance and good anti-corrosion performance.

[0030] In one embodiment, a method for preparing the non-ablative coating comprises the following steps:

[0031] S1. Preparing the ablation-free agent: placing the components of the ablation-free agent in a blender according to a proportion and stirring them evenly to obtain the ablation-free agent;

[0032] S2. Coating of non-ablative agent: evenly coat the non-ablative agent on the surface of the friction block, dry it naturally, and form a non-ablative coating on the surface of the friction block.

[0033] In step S1, based on the mass percentage of the ablative agent, the components are placed in a mixer according to the ratio of 15.0-25.0wt% of ethanol, 4.0-8.0wt% of organosilicon-modified phenolic resin, 45.0-60.0wt% of zirconium oxide, 5.0-8.0wt% of chromium oxide green, 6.0-10.0wt% of zinc powder, 3.0-6.0wt% of sodium bicarbonate, 1.0-2.0wt% of surfactant, and 2.0-4.0wt% of thickener. In one embodiment, the speed of the mixer is 200-240r / min, such as any value of 200-240r / min, 210r / min, 230r / min, or 240r / min; the stirring time is 5-7min, such as any value of 5min, 6min, or 7min. In one embodiment, in order to increase the contact area between the ablation-free agent and the brake pad and improve the performance of the brake pad, the zinc powder is flake zinc powder, and the D50 of the zinc powder is 13 to 45 μm, for example, it can be any value within the range of 13 to 45 μm, such as 13 μm, 20 μm, 30 μm, 40 μm or 45 μm.

[0034] In step S2, the coating thickness of the non-ablative agent is 0.1-0.2 mm, for example, any value in the range of 0.1-0.2 mm, such as 0.1 mm, 0.15 mm or 0.2 mm. The present application does not limit the coating method of the non-ablative agent, as long as the non-ablative agent can be evenly coated on the surface of the friction block, for example, the non-ablative agent can be coated on the surface of the friction block using a roller.

[0035] In one embodiment, a protective layer formed by plastic spraying is provided on the surface of the steel back away from the ablation-free coating. Plastic spraying is to spray plastic powder on the surface of the steel back by electrostatic spraying to improve its corrosion resistance. Exemplarily, the temperature of the plastic spraying is 180-220°C, such as any value of 180°C, 200°C or 220°C, and the time of the plastic spraying is 20-30min, such as any value of 20min, 25min or 30min. There is no restriction on the type of plastic powder in this application, and plastic powder commonly used in this field can be used. In this application, the plastic spraying can not only improve the corrosion resistance of the steel back, but also realize the curing of the ablation-free agent during the plastic spraying process. The brake pad of this application, after the ablation-free agent is coated on the surface of the friction block, can use the plastic spraying to complete the curing of the ablation-free agent, without the need for additional high-temperature processes, which can simplify the process flow and reduce costs.

[0036] The technical scheme of the present invention is described in detail below through several specific examples. Unless otherwise specified, the raw materials and reagents used in the following examples are all commercially available products, or can be prepared by conventional methods in the art, and the instruments used in the examples are all commercially available.

[0037] Example 1

[0038] The ablative agent for the brake pad of this embodiment includes the following components, in terms of mass percentage of the ablative agent: 15.0wt% ethanol, 8.0wt% organosilicon-modified phenolic resin, 60.0wt% zirconium oxide, 5.0wt% chromium oxide green, 6.0wt% zinc powder, 3.0wt% sodium bicarbonate, 1.0wt% surfactant, and 2.0wt% thickener. In this embodiment, the brake pad includes a friction block and a steel back. The components of the ablative agent are introduced into a high-speed mixer at a time according to this ratio, and mixed at a speed of 240r / min for 5min to obtain the ablative agent. The ablative agent is evenly coated on the surface of the friction plate using a roller, and the coating thickness is 0.1mm. After natural drying, the surface of the steel back is sprayed with plastic, and the treatment temperature is 200°C and the treatment time is 27min.

[0039] In this embodiment, the gel time of the silicon-modified phenolic resin is 30s / 165°C, the D50 of zirconium oxide is 1.5 μm, the D50 of zinc powder is 45 μm, the surfactant is polyethylene glycol octylphenyl ether, and the thickener is hydroxyethyl cellulose.

[0040] Example 2

[0041] The ablative agent for the brake pad of this embodiment includes the following components, in terms of mass percentage of the ablative agent: 25.0wt% ethanol, 4.0wt% organosilicon-modified phenolic resin, 45.0wt% zirconium oxide, 8.0wt% chromium oxide green, 6.0wt% zinc powder, 6.0wt% sodium bicarbonate, 2.0wt% surfactant, and 4.0wt% thickener. In this embodiment, the brake pad includes a friction block and a steel back. The components of the ablative agent are introduced into a high-speed mixer at a time according to this ratio, and mixed at a speed of 200r / min for 7min to obtain the ablative agent. The ablative agent is evenly coated on the surface of the friction block using a roller, and the coating thickness is 0.2mm. After natural drying, the surface of the steel back is sprayed with plastic, and the treatment temperature is 180°C and the treatment time is 30min.

[0042] In this embodiment, the gel time of the silicon-modified phenolic resin is 51 s / 165° C., the D50 of zirconium oxide is 6.0 μm, the D50 of zinc powder is 13 μm, the surfactant is fatty alcohol polyoxyethylene ether, and the thickener is polyvinyl alcohol.

[0043] Example 3

[0044] The ablation-free agent for the brake pad of this embodiment includes the following components, in terms of mass percentage of the ablation-free agent: 18.0wt% ethanol, 6.0wt% organosilicon-modified phenolic resin, 51.5wt% zirconium oxide, 6.0wt% chromium oxide green, 10.0wt% zinc powder, 4.0wt% sodium bicarbonate, 1.5wt% surfactant, and 3.0wt% thickener. In this embodiment, the brake pad includes a friction block and a steel back. The components of the ablation-free agent are introduced into a high-speed mixer at one time according to this ratio, and mixed at a speed of 220r / min for 6min to obtain the ablation-free agent. The ablation-free agent is evenly coated on the surface of the friction block using a roller, and the coating thickness is 0.15mm. After natural drying, the surface of the steel back is sprayed with plastic, and the treatment temperature is 200°C and the treatment time is 27min.

[0045] In this embodiment, the gel time of the silicon-modified phenolic resin is 40s / 165°C, the D50 of zirconium oxide is 4.0 μm, the D50 of zinc powder is 30 μm, the surfactant is fatty alcohol polyoxyethylene ether, and the thickener is hydroxyethyl cellulose.

[0046] Example 4

[0047] The ablative agent for brake pads in this embodiment includes the following components, in terms of mass percentage of the ablative agent: 20.0wt% ethanol, 5.0wt% organosilicon-modified phenolic resin, 55.0wt% zirconium oxide, 5.0wt% chromium oxide green, 7.0wt% zinc powder, 5.0wt% sodium bicarbonate, 1.0wt% surfactant, and 2.0wt% thickener. In this embodiment, the brake pad includes a friction block and a steel back. The components of the ablative agent are introduced into a high-speed mixer at a time according to this ratio, and mixed at a speed of 210r / min for 6min to obtain the ablative agent. The ablative agent is evenly coated on the surface of the friction block using a roller, and the coating thickness is 0.1mm. After natural drying, the surface of the steel back is sprayed with plastic, and the treatment temperature is 220°C and the treatment time is 20min.

[0048] In this embodiment, the gel time of the silicon-modified phenolic resin is 45s / 165°C, the D50 of zirconium oxide is 3.0 μm, the D50 of zinc powder is 40.0 μm, the surfactant is fatty alcohol polyoxyethylene ether, and the thickener is hydroxyethyl cellulose.

[0049] Example 5

[0050] The ablation-free agent for the brake pad of this embodiment includes the following components, in terms of mass percentage of the ablation-free agent: 20.0wt% of ethanol, 6.0wt% of organosilicon-modified phenolic resin, 47.0wt% of zirconium oxide, 7.0wt% of chromium oxide green, 9.0wt% of zinc powder, 6.0wt% of sodium bicarbonate, 2.0wt% of surfactant, and 3.0wt% of thickener. In this embodiment, the brake pad includes a friction block and a steel back. The components of the ablation-free agent are introduced into a high-speed mixer at a time according to this ratio, and mixed at a speed of 200r / min for 7min to obtain the ablation-free agent. The ablation-free agent is evenly coated on the surface of the friction plate using a roller, and the coating thickness is 0.2mm. After natural drying, the surface of the steel back is sprayed with plastic, and the treatment temperature is 190°C and the treatment time is 28min.

[0051] In this embodiment, the gel time of the silicon-modified phenolic resin is 47s / 165°C, the D50 of zirconium oxide is 5.0 μm, the D50 of zinc powder is 35.0 μm, the surfactant is polyethylene glycol octylphenyl ether, and the thickener is hydroxyethyl cellulose.

[0052] The zinc powder in the above embodiments of the present application is all flake zinc powder.

[0053] The brake pads coated with the ablative agent on the surfaces of Examples 1 to 5 were subjected to a braking performance test according to the SAE J2522 test standard, and the brake pads were subjected to a neutral salt spray test according to the ISO 9227 standard to test the anti-rust performance of the brake pads. The test results are shown in Table 1:

[0054] Table 1: Braking performance and anti-rust performance of brake pads coated with ablation-free agent in Examples 1 to 5

[0055]

[0056] As can be seen from Table 1, after the brake pad is coated with the ablation-free agent prepared in the present application, the friction coefficient is greatly improved, and the Green μ section friction coefficient μ can be increased from 0.25 to above 0.37, and the initial braking performance is good; and after the salt spray test, there is no rust on the surface of the brake pad, indicating that the brake pad has good anti-corrosion performance.

[0057] The ablative-free agent for brake pads of the present invention has zirconium oxide, chromium oxide green, flake zinc powder and sodium bicarbonate added to the ablative-free agent, which can improve the initial braking performance of the brake pads. The organosilicon-modified phenolic resin-zinc powder-sodium bicarbonate ternary composite can improve the hydrophobicity of the ablative-free agent matrix and the anti-rust performance of the brake pads through the synergistic effect of organosilicon-modified phenolic resin, zinc powder and sodium bicarbonate. In addition, the ablative-free agent of the present invention does not contain toxic reagents, is environmentally friendly and non-toxic, and is easy to prepare; further, when the ablative-free agent is coated on the brake pad, it can be directly coated, and the curing of the ablative-free agent can be completed by plastic spraying, eliminating the additional high-temperature curing process, which can greatly reduce the cost. Therefore, the present invention effectively overcomes some practical problems in the prior art and has a high utilization value and use significance.

[0058] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A non-ablation agent for brake pads, characterized in that: Calculated by mass percentage of the ablation-free agent, the ablation-free agent includes the following components: 15.0-25.0wt% of ethanol, 4.0-8.0wt% of organosilicon-modified phenolic resin, 45.0-60.0wt% of zirconium oxide, 5.0-8.0wt% of chromium oxide green, 6.0-10.0wt% of zinc powder, 3.0-6.0wt% of sodium bicarbonate, 1.0-2.0wt% of surfactant, and 2.0-4.0wt% of thickener.

2. The ablation-free agent for brake pads according to claim 1, characterized in that: The organosilicon-modified phenolic resin has a gel time of 30 to 51 seconds at 165°C.

3. The ablation-free agent for brake pads according to claim 1, characterized in that: The D50 of the zirconium oxide is 1.5 to 6.0 μm.

4. The ablation-free agent for brake pads according to claim 1, characterized in that: The zinc powder is flake zinc powder, and the D50 of the zinc powder is 13-45 μm.

5. The ablation-free agent for brake pads according to claim 1, characterized in that: The surfactant includes any one of polyethylene glycol octylphenyl ether and fatty alcohol polyoxyethylene ether; the thickener includes any one of hydroxyethyl cellulose and polyvinyl alcohol.

6. A brake pad, characterized in that: The brake pad comprises a friction block and a steel back, and the surface of the friction block is coated with a non-ablation coating made of the non-ablation agent for the brake pad according to any one of claims 1 to 5.

7. The brake pad according to claim 6, characterized in that: The preparation of the ablation-free coating comprises the following steps: Preparation of the ablation-free agent: placing ethanol, organosilicon-modified phenolic resin, zirconium oxide, chromium oxide green, zinc powder, sodium bicarbonate, a surfactant, and a thickener in a blender according to the raw material ratio and stirring evenly to obtain the ablation-free agent; Ablation-free agent coating: the ablation-free agent is uniformly coated on the surface of the friction block and dried naturally to form an ablation-free coating on the surface of the friction block.

8. The brake pad according to claim 7, characterized in that: The rotating speed of the stirrer is 200-240 r / min, and the stirring time is 5-7 min.

9. The brake pad according to claim 7, characterized in that: The coating thickness of the ablation-free agent is 0.1 to 0.2 mm.

10. The brake pad according to claim 6, characterized in that: A protective layer formed by spraying is arranged on the surface of the steel back away from the ablation-free coating. The temperature of the spraying is 180-220° C. and the time of the spraying is 20-30 minutes.

Citation Information

Patent Citations

  • Non-fired friction coating for brake pad coating and preparing method of non-fired friction coating

    CN104482087A

  • Brake pad coating

    CN109099082A

  • Environment-friendly friction material and brake pad and preparation method based on environment-friendly friction material

    CN110242691A

  • Ablation-free agent for brake pad, preparation method and application method thereof, and brake pad

    CN110903731A

  • Copper-free NAO friction material, brake pad and preparation method

    CN112745802A